2014
DOI: 10.7575/aiac.alls.v.5n.4p.102
|View full text |Cite
|
Sign up to set email alerts
|

English Language Writing Anxiety among Final Year Engineering Undergraduates in University Putra Malaysia

Abstract: Second Language Writing Anxiety (SLWA) is considered one of the most crucial factors affecting all second language learning. This study focused on a group of final year Engineering students' English Language writing anxiety (N=93) in relation to their gender, race and MUET results. The findings showed that the the male gender, Chinese and MUET band 4 participants faced higher levels of anxiety as compared to the other groups respectively. Somatic anxiety was recorded to be the highest subscale of anxiety faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 5 publications
2
18
3
Order By: Relevance
“…The language learning anxiety of engineering students as learners of English as a foreign language has been investigated in relation to a range of factors, such as gender, experience of speaking English with foreigners, and duration of English learning (Khunnawut 2011). It has also been reported that engineering students experience somatic anxiety when learning English (Min & Rahmat 2014). This most common form of language learning anxiety refers to 'one's perception of the physiological effects of the anxiety experience, as reflected in increase in arousal of unpleasant feelings, such as nervousness and tension' (Cheng 2004, p. 316).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The language learning anxiety of engineering students as learners of English as a foreign language has been investigated in relation to a range of factors, such as gender, experience of speaking English with foreigners, and duration of English learning (Khunnawut 2011). It has also been reported that engineering students experience somatic anxiety when learning English (Min & Rahmat 2014). This most common form of language learning anxiety refers to 'one's perception of the physiological effects of the anxiety experience, as reflected in increase in arousal of unpleasant feelings, such as nervousness and tension' (Cheng 2004, p. 316).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The aim was not to generalise. Following the focus of previous studies (Khunnawut 2011, Min & Rahmat 2014, the researchers were simply interested in factors that might explain language learning anxiety in engineering students as learners of English.…”
Section: Research Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon had been investigated in relation to a range of factors, such as gender, experience of speaking English with foreigners, and duration of English learning (Khunnawut, 2011). It had been reported that engineering students experience somatic anxiety when learning English (Min & Rahmat, 2014). This most common form of language anxiety refers to 'one's perception of the physiological effects of the anxiety experience, as reflected in increase in arousal of unpleasant feelings, such as nervousness and tension' (Cheng, 2004, p. 316).…”
Section: Literature Reviewmentioning
confidence: 99%